2019
DOI: 10.33102/uij.vol26no.90
|View full text |Cite
|
Sign up to set email alerts
|

Antidiabetic and Antioxidant Capacities of Local Banana Peels Extract by Using Subcritical Water Extraction Technique

Abstract: Banana peels has been shown to possess strong antioxidant which may exhibit protective responses against reactive oxygen species through free radicals scavenging and breaking the autoxidative chain reaction and restore the ‘redox homeostasis’ state. Subcritical water extraction method was used by using water as the solvent and increasing the temperature to between 100 and 374°C and keeping the pressure high enough to maintain the liquid state allowing the dielectric constant (ε) of water becomes like that of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 21 publications
1
3
0
Order By: Relevance
“…used this assay in the study of banana ( Musa cavendish ) peel wherein the authors reported a higher TPC (64.55 mg of Trolox equivalents/g of dry matter) that was also higher than in other assays (DPPH, FRAP, and ABTS) used. However, the DPPH radical assay (2,2-diphenyl-1-picrylhydrazyl) is used in the BPE and the isolated BP antioxidant compound evaluation due to its economical feature and minimum required time for extraction. ,, …”
Section: Banana Peel Phenolic Compounds and Antioxidant Activitysupporting
confidence: 91%
See 2 more Smart Citations
“…used this assay in the study of banana ( Musa cavendish ) peel wherein the authors reported a higher TPC (64.55 mg of Trolox equivalents/g of dry matter) that was also higher than in other assays (DPPH, FRAP, and ABTS) used. However, the DPPH radical assay (2,2-diphenyl-1-picrylhydrazyl) is used in the BPE and the isolated BP antioxidant compound evaluation due to its economical feature and minimum required time for extraction. ,, …”
Section: Banana Peel Phenolic Compounds and Antioxidant Activitysupporting
confidence: 91%
“…However, the DPPH radical assay (2,2-diphenyl-1-picrylhydrazyl) is used in the BPE and the isolated BP antioxidant compound evaluation due to its economical feature and minimum required time for extraction. 41,44,4 Paper spray-mass spectrometry is also reported for evaluation of the chemical profile of the Prata variety of ripe Musa sp. banana peel flour.…”
Section: Quality Impairment Of Meat and Meat Products Due To Oxidativ...mentioning
confidence: 99%
See 1 more Smart Citation
“…As a result, research on phytochemicals that may serve as possible adjuvant medicines was conducted in the past year. Since diabetes is linked to oxidative stress, antioxidant chemicals from FBPs will emerge as a more enticing substitute (Ishak et al 2019 ). Many authors studied the antidiabetic activity in FBPs.…”
Section: Nutraceutical Potential and Health Benefits Of Fbpsmentioning
confidence: 99%